Digitalisation of information and management optimisation in Multiple Victim Incidents. Analytical study. - Navid Behzadi Koochnai; Raúl Muñoz Romo; Nicolás Riera López; Rafael Caballero Cubedo; Soledad Gómez de la Oliva; Teresa Martin de Rosales Cabrera; Almudena Castaño Reguillo (PLoS ONE, 2024)
Introduction Triage is a crucial tool for managing a Multiple Victim Incident (MVI). One particularly problematic issue is the communication of results to the chain of command and control. Favourable data exists to suggest that digital triage can improve some features of analogue triage. Within this context we have witnessed the emergence of the Valkyries Project, which is working to develop strategies to respond to MVIs, and especially cross-border incidents. To that end, an IT platform called "SIGRUN" has been created which distributes, in real time, all the information to optimise MVI management. A full-scale simulation, held on the Spain-Portugal border and featuring contributions from different institutions on both sides of the border, put to the test the role of information digitalisation in this type of incidents. Objective To evaluate the impact of the synchronous digitalisation of information on the optimal management of Multiple Victim Incidents. Method Clinical evaluation study carried out on a cross-border simulation between Spain and Portugal. A Minimum Data Set (MDS) was established by means of a modified Delphi by a group of experts. The digital platform "SIGRUN" integrated all the information, relaying it in real time to the chain of command and control. Each country assigned two teams that would carry out digital and analogue triage synchronously. Analogue triage variables were gathered by observers accompanying the first responders. Digital triage times were recorded automatically. Each case was evaluated and classified simultaneously by the two participating teams, to carry out a reliability study in a real time scenario. Results The total duration of the managing of the incident in the A group of countries involved compared to the B group was 72.5 minutes as opposed to 73 minutes. The total digital assistance triage (AT) time was 37.5 seconds in the digital group, as opposed to 32 minutes in the analogue group. Total evacuation (ET) time was 28 minutes in the digital group compared with 65 minutes in the analogue group. The average differences in total times between the analogue and the digital system, both for primary and secondary evaluation, were statistically significant: p = 0.048 and p = 0.000 respectively. For the "red" category, AT obtained a sensitivity of 100%, also for ET, while with regard to AT safety it obtained a PPV of 61.54% and an NPV of 100%, and for ET it obtained a PPV of 83.33% and an NPV of 100%. For the analogue group, for AT it obtained a sensitivity of 62.50%, for ET, 70%, for AT safety it obtained a PPV of 45.45% and an NPV of 92.31%, while for ET it obtained a PPV of 70% and an NPV of 92.50%. The gap analysis obtained a Kappa index of 0.7674. Conclusion The triage system using the developed digital tool demonstrated its validity compared to the analogue tool, as a result of which its use is recommended.